PEMBERIAN KOMPOS TANDAN KOSONG KELAPA SAWIT DAN JARAK TANAM PADA KEDELAI EDAMAME (Glycine max (L) Merril) - Sahputra, Norman; Yulia, Arnis En; Silvina, Fetmi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research aims to look at the giving of various dose combinations Palm Empty Fruit Bunch compost (PEFB) and spacing on the growth and yield of edamame soybean and to get the best treatment combination between compost PEFB and planting distance of the growth and production of edamame soybean. Research conducted in the experimental field Fakultas Pertanian Universitas Riau. Research period on June until August 2014. Experiments with 4 x 3 factorial using a randomized block design (RBD). The first factor is composting palm empty fruit bunch consisting of 4 levels (5, 10, 15 and 20 ton / ha). The second factor is planting distance consists of 3 levels (10 × 20, 15 × 20 and 20 × 20 cm), combination is repeated three times respectively. The efect of each treatment combination known through Duncan multiple test 5% level. Parameters measured were leaf area, root nodule effective, flowering time, the percentage of pods pithy, pithy number of pods per plant and yield per plot. The results showed that the combination of composting palm empty fruit bunch with planting distance effect on the effective root nodules, number of pods pithy planting, production per plot but did not affect the leaf area, flowering time, the percentage of pods pithy. The highest production was found in compost treatment of palm empty fruit bunches of 20 ton / ha and distance of (15 × 20) cm with a production that is 1717.2 g / plot. Keyword : edamame soybeans, composting palm empty fruit bunch, spacing on